The effects of different types of written corrective feedback on studentsâ€™ texting mistakes - Hasan GÃ¼ner Berkant; Nuriye Batmaz Derer; Ozgur Kursad Derer (English Language Teaching Educational Journal, 2020)
The main purpose of this research was to investigate the effects of different types of written corrective feedback on students' texting mistakes in English lessons. In the study, a mixed model including quantitative and qualitative methods was engaged. Two-factor ANOVA was used for mixed measurements to test the significance of the difference between the error numbers of the three types of feedback except direct feedback. The qualitative data of the study were collected by examining the texts and the interviews about the effect of the four feedbacks were made with the students. Content analysis and descriptive analysis were performed. At the end of the study, in the quantitative findings obtained, the most effective type of feedback is the underlined feedback. As for the qualitative findings obtained from the students' opinions, the feedback type in which the error is coded and the information is given is the most effective type.